UJI POTENSI DAUN MUDA SUNGKAI (Peronema canescens) UNTUK KESEHATAN (IMUNITAS) PADA MENCIT (Mus.muculus) - Yani, Ariefa Primair; Yenita, Yenita; Ansori, Irwandi; Irwanto, Riko (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - In Lembak delapan Tribes traditional medicine, water decoction of the Sungkai leaves is used for raw material fever-lowering drugs (antipyretics), to maintain good health, and for malaria drug. This study aims to test the effectiveness of the infusion of leaves P. canescens to maintain goodhelth (immunity) in mice (Mus muculus). The Young leaves of Sungkai (P.canensces) was extracted by maceration method using 96% alcohol solvent. This study used 25 male mice strain Swiss Webster with 7-8 weeks old, with a body weight ranging from 30 g. At the immunity test, mice were divided into 5 groups. Group 1 (negative control) were given distilled water, group 2 (positive control) was given imunos 0.07 mg / kg bw, for the three treatment groups were given of the extract dose of 0.186 mg Sungkai / Kg mm, 0.375 mg / kg bw, and 0, 5625 mg / kg bw. Treatment with one gavage, with a span of 24 hours. After the calculation is done by taking a blood leukocytes from mice tail. Data were analyzed using ANOVA tables and followed by LSD test. The results showed thatÂ  the Immunity test dose of the most effective in helping the immune system with a dose of 0.567 mg Sungkai extract / kg bw, tends to increase by 36% leukocytes, better than than the comparator dose (imunos) leukosit only increase the amount by 23%. Â Keywords: sungkai,immunity, mice